2022
DOI: 10.1371/journal.pmed.1003895
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant discontinuation before or during pregnancy and risk of psychiatric emergency in Denmark: A population-based propensity score–matched cohort study

Abstract: Background Women prescribed antidepressants face the dilemma of whether or not to continue their treatment during pregnancy. Currently, limited evidence is available on the efficacy of continuing versus discontinuing antidepressant treatment during pregnancy to aid their decision. We aimed to estimate whether antidepressant discontinuation before or during pregnancy was associated with an increased risk of psychiatric emergency (ascertained by psychiatric admission or emergency room visit), a proxy measure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Pregnant women are generally advised to discuss with their prescribing physician about pharmacological treatment options during pregnancy; however, many women experience high decisional conflict in the decision-making. [7][8][9][10][11] Most available studies investigating the effectiveness and safety of AD during pregnancy, however, have defined AD exposure in a simplistic way using a fixed time window and without taking into account the nature of long-term treatment and changes in dosage as well as indication. [12][13][14] A recent study using Danish registry linked data also highlighted the differences in psychiatric outcomes with regard to the timing of discontinuation during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women are generally advised to discuss with their prescribing physician about pharmacological treatment options during pregnancy; however, many women experience high decisional conflict in the decision-making. [7][8][9][10][11] Most available studies investigating the effectiveness and safety of AD during pregnancy, however, have defined AD exposure in a simplistic way using a fixed time window and without taking into account the nature of long-term treatment and changes in dosage as well as indication. [12][13][14] A recent study using Danish registry linked data also highlighted the differences in psychiatric outcomes with regard to the timing of discontinuation during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] A recent study using Danish registry linked data also highlighted the differences in psychiatric outcomes with regard to the timing of discontinuation during pregnancy. 10 In addition, studies using register-based data usually rely on the simple assumptions of one defined daily dose (DDD) or one tablet per day to model duration of treatment. 15,16 Recently, a novel method generating drug use patterns from prescription dispensations (PRE2DUP) was developed and validated on the Finnish prescription register.…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of psycholeptics was defined as filling a psycholeptic (ATC code N05) prescription, including antipsychotics, anxiolytics, hypnotics, and sedatives, post partum without psycholeptic prescriptions filled in the 6 months before and during pregnancy. A psychiatric emergency was defined as having emergency department visits or inpatient treatment for mental disorders ( ICD-10 F codes) . Self-harm was defined based on ICD-8 and ICD-10 codes derived from a validated coding algorithm (definition in the eMethods in Supplement 1).…”
Section: Methodsmentioning
confidence: 99%
“…The risk was more pronounced among women with severe and recurrent depression (risk ratio, 2.30; 95% CI, 1.58-3.35). A recent study in Denmark found that pregnant women who discontinued antidepressants during but not before pregnancy had an increased risk of psychiatric emergency during pregnancy compared with continuers . Of note, antidepressant use patterns before and during pregnancy are complex, especially the timing of discontinuation .…”
Section: Introductionmentioning
confidence: 99%
“…Limited evidence exists on the effectiveness of antidepressants in pregnancy or as a preventive treatment of postnatal mental illness in high‐risk patients (Bayrampour et al, 2020; Liu et al, 2022; Molyneaux et al, 2014; Sharma, 2017). The few available studies focus mainly on depression (Bayrampour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%